2016
DOI: 10.1016/j.renene.2015.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Structural topology optimization of the transition piece for an offshore wind turbine with jacket foundation

Abstract: a b s t r a c tThe transition piece of a fixed offshore wind turbine is a reinforced part of the support structure that is connected to the wind turbine tower. These structural elements present unique features and are critical components of offshore wind turbines; designed to resist strong bending moments, shear forces and axial loads coming from cyclic environmental loads, such as wind and wave loads, acting during their complete design life of 20 years. Well designed and manufactured transition pieces with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The EADS (European Aeronautic Defence and Space Company) Innovation Works and EOS (a German SLM systems and service supplier) cooperated in the manufacture of Airbus A320 and A380 brackets with optimised topology. The results showed an obvious reduction in weight and raw material consumption [12,18,22]. However, the majority of the studies on TO and SLM focused on micro-lattice structured parts.…”
Section: Introductionmentioning
confidence: 98%
“…The EADS (European Aeronautic Defence and Space Company) Innovation Works and EOS (a German SLM systems and service supplier) cooperated in the manufacture of Airbus A320 and A380 brackets with optimised topology. The results showed an obvious reduction in weight and raw material consumption [12,18,22]. However, the majority of the studies on TO and SLM focused on micro-lattice structured parts.…”
Section: Introductionmentioning
confidence: 98%
“…Using the proposed synthesis technique, structures have been made to grow from a simple generic base structure to a complex form along an optimized pathway formed by a series of intermediate steps. Lee et al 16 optimized the transition piece for an offshore wind turbine with jacket foundation by topology optimization method and found that the optimized solution was lighter and extended the fatigue life significantly. Tian et al 17 designed the offshore platform jacket structure using the topology optimization method and obtained an optimal structure with lighter weight and large ultimate carrying capacity ability.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal design was searched for according to tower mass and fabrication complexity. Lee et al [42] studied the structural topology optimisation of the transition piece for an OWT with jacket foundation. Lighter structure was achieved with the structural topology optimisation, demonstrating the topology optimisation can be effective and speeding up the total design cycle.…”
Section: Introductionmentioning
confidence: 99%